POLITICAL EPISTEMOLOGY AT THE TURN OF THE CENTURY: COMMUNICATIVE TRANSFORMATIONS AND THE UKRAINIAN CONTEXT - Kleshnуa Hanna; Ordenov, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. Political epistemology remains one of the least systematized philosophical sub-disciplines despite the rapid development of research on epistemic injustice, post-truth, and communicative transformations over the past twenty-five years. At the same time, contemporary political crises, information wars, and algorithmically mediated communication significantly transform the problem field of political epistemology. The aim and tasks. The aim of the article is to reconstruct the development of political epistemology at the turn of the 20th–21st centuries by identifying the main generations of research and determining the contribution of Ukrainian philosophical thought to the contemporary stage of this discipline. Research methods. The methodological basis combines normative, critical-analytical, and post-normative approaches to the philosophical analysis of communicative processes. The study employs historical-philosophical reconstruction, comparative analysis, and conceptual analysis of contemporary theories of political communication and social epistemology. Research results. Three generations of political epistemology are identified. The first generation focuses on epistemic injustice and mechanisms of exclusion from epistemic communities. The second generation shifts attention to the institutional conditions of democratic knowledge production and political communication. The third generation emerges in response to information wars, the crisis of trust, and algorithmically mediated communication and may be characterized as “defensive political epistemology.” The study analyzes the existential crisis of communicative practices, the concept of controlled chaos as a mechanism of radical social construction, the neoliberal transformation of democratic institutions, and the phenomenon of demodernization. The concept of “epistemic fatigue” is proposed to describe the systematic erosion of motivation for cognitive activity under conditions of persistent informational and ontological pressure. Discussion. The analysis demonstrates a gradual expansion of the research object in political epistemology: from interpersonal epistemic relations to institutional conditions of knowledge production and further to the architecture of the contemporary information environment. Particular importance is attributed to the integration of political communication into epistemological analysis. Conclusions. Political epistemology has evolved from a marginal field into one of the central directions of contemporary philosophical reflection on communication and power. Under current conditions, the key issue becomes not only the achievement of truth but also the preservation of the conditions under which truth remains possible. Ukrainian philosophical concepts of communicative sovereignty and epistemic security architecture expand the analytical potential of contemporary political epistemology.